2007
DOI: 10.1590/s1516-89132007000300013
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and morphological aspects of salivary glands of the predator Brontocoris tabidus (Heteroptera: Pentatomidae)

Abstract: The aim of this work was to study the feeding habits of the predator Brontocoris tabidus (Heteroptera: Pentatomidae) analyzing the salivary gland complex (SGC). The SGC was dissected and subjected to histological analyses and biochemical assays. Results showed that a pair of bilobed principal salivary glands and one pair of tubular accessory salivary glands form the SGC and different parts of salivary gland synthesizes similar substances.Lipases, α-amylase and trypsin-like enzymes were detected at both lobes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 18 publications
6
55
0
1
Order By: Relevance
“…Zoophytophagous predators feed on prey and/or on plants (Agrawal et al, 1999;Eubanks and Denno;Coll and Guershon, 2002;Azevedo et al, 2007;Guedes et al, 2007) with benefits for biological control of insect pests by improving the maintenance of the populations of these natural enemies during periods of prey shortage (Cocuzza et al, 1997). However, the morphological features of the reproductive organs and the fecundity of predatory Pentatomidae can be affected by factors such as unfavorable environmental conditions and quantity or quality of the food (Lemos et al, 2005a;2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Zoophytophagous predators feed on prey and/or on plants (Agrawal et al, 1999;Eubanks and Denno;Coll and Guershon, 2002;Azevedo et al, 2007;Guedes et al, 2007) with benefits for biological control of insect pests by improving the maintenance of the populations of these natural enemies during periods of prey shortage (Cocuzza et al, 1997). However, the morphological features of the reproductive organs and the fecundity of predatory Pentatomidae can be affected by factors such as unfavorable environmental conditions and quantity or quality of the food (Lemos et al, 2005a;2005b).…”
Section: Introductionmentioning
confidence: 99%
“…After the 3rd instar, P. maculiventris shows high midgut activities of β-glucosidase and amylase, indicating their ability to use β-glucosides such as salicine, amygdaline, arbutine, and gentibiose, among others from plant starch digestion (Stamopoulos et al, 1993). The high amylase activity not only indicates its potential to digest the starch, the major glycoside reserve found in plants, but also other polysaccharides and dextrines from glycogen, the major animal cell glycoside reservoir (Cohen, 1990;Stamopoulos et al, 1993) what correlates with amylase presence in neotropic Asopinae species Podisus nigrispinus and Brontocoris tabidus (Oliveira et al, 2006;Azevedo et al, 2007). Lygus hesperus is a good example of a phytophagous species with a propensity to switch the feeding between the plant and animal.…”
Section: Discussion Predatory Switching Enzymesmentioning
confidence: 96%
“…In this line of research, other studies have characterized the enzyme pattern of the content of salivary glands and the midgut of the predator Brontocoris tabidus, indicating that this insect may be considered an obligate zoophytophagous species (AZEVEDO et al, 2007;GUEDES et al, 2007;OLIVEIRA et al, 2006). Regarding the same subject, other studies have shown that Asopinae predators present a "standard" enzyme in the salivary gland in function of the feeding behavior.…”
Section: Scientific Contributions In the Field Of Biochemistrymentioning
confidence: 95%
“…In 1995, at the Federal University of Viçosa (UFV), the first doctoral thesis was defended which dealt specifically with Asopinae predators whose theme was "Artificial diet for Podisus nigrispinus (Dallas) and influence on its ability for predation of Anticarsia gemmatalis Hubner" (SAAVEDRA, 1995). Through years of research and investigations, advances with Asopinae predators have resulted in various studies of biology and plant health such as: increasing the number of species reported (THOMAS, 1992), definition and presentation of the main species for biological control programs (PIRES et al, 2009a;THOMAS, 1992), increase in the number of institutions collaborating in this line of research (Federal University of Viçosa -UFV, Federal University of Lavras -UFLA, Federal University of Mato Grosso -UFMT, Federal University of Vales do Jequitinhonha and Mucuri -UFVJM, Federal University of Paraíba -UFPB, Federal University of Grande Dourados -UFGD, Federal University of Rio Grande do Sul -UFRGS, Federal University of Minas Gerais -UFMG, Federal University of Pará -UFPA, Federal Rural Univeristy of Pernambuco -UFRPE and EMBRAPA), evolution of equipment for mass rearing and techniques and form of management (MOLINA-RUGAMA et al, 1998;PELÚZIO, 2012;PIRES et al, 2006;ZANUNCIO et al, 1994a), accommodation and ambience (MEDEIROS et al, 2003;SANTOS et al, 2005), physiology and internal and external morphology (AZEVEDO et al, 2007;GUEDES et al, 2007;LEMOS et al, 2006;2005a;SOARES et al, 2011;SÁ et al, 2013), studies on sensory and (ALDRICH et al, 1997;CORACINI et al, 1999;TORRES et al, 1997a) behavioral aspects (CARVALHO et al, 1995;1994;FERREIRA et al, 2008;LEMOS et al, 2005d;PIRES et al, 2010a;SAAVEDRA et al, 1997;SILVA et al, 2012;VIVIAN et al, 2002), toxicology, with focus on studies on selectivity of insecticides ...…”
Section: Introductionmentioning
confidence: 99%